A Google Sites-Based Virtual Gallery: A Means of Arts and Culture Appreciation for Middle School Students - Wanda Syahriana; A. Baetal Mukaddas; Johar Linda (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The low level of student appreciation for arts and culture subjects and the limitations of conventional learning media in documenting and exhibiting student works on an ongoing basis often hinder the interactive teaching and learning process. This study aims to determine the effect of using a Google Sites-based virtual gallery on students' level of art and culture appreciation, describe student responses, and identify the advantages and disadvantages of this media in learning. This study uses a quantitative approach with a quasi-experimental method through a one-group pretest–posttest design. The research subjects consisted of 30 students selected from one class. Data collection techniques include art appreciation tests (pretest and posttest), student response questionnaires, observations, and interviews. Quantitative data analysis used the Shapiro–Wilk normality test and paired sample t-test through the SPSS program version 25, while qualitative data were analyzed descriptively. The results showed an increase in the average value of student appreciation from 55.60 in the pretest to 59.27 in the posttest. The paired sample t-test produced a significant value of 0.011 (p < 0.05), which proves the positive and significant influence of the implementation of the virtual gallery on students' art appreciation. Student responses were in the positive category for the learning material, media display, and technical aspects. The advantages of this media include ease of access and increased motivation to learn, despite its dependence on internet connection and limited interactive features. Contribution: This study provides a contribution in the form of recommendations for the use of Google Sites-based virtual galleries as an effective alternative learning medium to increase appreciation of arts and culture at the junior high school level.